2017
DOI: 10.1155/2017/3164375
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular Responses of Human Retinal Cells to Infection with Dengue Virus

Abstract: Recent clinical reports indicate that infection with dengue virus (DENV) commonly has ocular manifestations. The most serious threat to vision is dengue retinopathy, including retinal vasculopathy and macular edema. Mechanisms of retinopathy are unstudied, but observations in patients implicate retinal pigment epithelial cells and retinal endothelial cells. Human retinal cells were inoculated with DENV-2 and monitored for up to 72 hours. Epithelial and endothelial cells supported DENV replication and release, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 69 publications
1
20
0
Order By: Relevance
“…The low susceptibility of HUVEC (18) and MDM (47,48) to DENV infection in vitro might account for the observed lack of detectable induction of extracellular FH in these cells. To analyze this, responses were evaluated in another EC transformed cell line (HPV E6/E7-transduced human retinal endothelial cells [HREC]), which have low susceptibility to DENV infection, and ARPE-19 retinal pigment epithelial cells, which have high susceptibility to DENV infection (49). Consistent with the results in HUVEC and MDM, the levels of FB and FH mRNA were significantly increased in DENV-infected HREC and ARPE-19 cells at 48 hpi (Fig.…”
Section: Resultssupporting
confidence: 61%
“…The low susceptibility of HUVEC (18) and MDM (47,48) to DENV infection in vitro might account for the observed lack of detectable induction of extracellular FH in these cells. To analyze this, responses were evaluated in another EC transformed cell line (HPV E6/E7-transduced human retinal endothelial cells [HREC]), which have low susceptibility to DENV infection, and ARPE-19 retinal pigment epithelial cells, which have high susceptibility to DENV infection (49). Consistent with the results in HUVEC and MDM, the levels of FB and FH mRNA were significantly increased in DENV-infected HREC and ARPE-19 cells at 48 hpi (Fig.…”
Section: Resultssupporting
confidence: 61%
“…Smith et al 2017 have recently shown that retinal epithelial and endothelial cells are susceptible to DENV infection with cytopathic effects in epithelial cells. The infection decreased the epithelial barrier integrity while the endothelial junctions were intact which correlated with the clinically observed loss of RPE in DENV infected patients [ 68 ].…”
Section: Flaviviruses and Ocular Complicationsmentioning
confidence: 98%
“…Initial studies using human retinal cells and new in vivo models, most commonly in rodents, are providing illuminating information in this regard. While this work is in its infancy, research from several groups has focused on the potential role of the human retinal pigment epithelial cell as a key cell in providing access to the eye, supporting DENV, ZIKV and EBOV replication and generating a strong innate anti‐viral response . Studies of infections induced in mice by local or systemic ZIKV inoculation demonstrate that, as well as retinal pigment epithelial cells, Mueller cells, also may be primary targets for these viruses .…”
Section: Resultsmentioning
confidence: 99%
“…While this work is in its infancy, research from several groups has focused on the potential role of the human retinal pigment epithelial cell as a key cell in providing access to the eye, supporting DENV, ZIKV and EBOV replication and generating a strong innate anti-viral response. [82][83][84] Studies of infections induced in mice by local or systemic ZIKV inoculation demonstrate that, as well as retinal pigment epithelial cells, Mueller cells, also may be primary targets for these viruses. 85,86 As these investigations expand, they may identify opportunities to develop novel anti-viral drugs targeted at key pathogenic viral and/or infected host cell molecules.…”
Section: Discussionmentioning
confidence: 99%